NALAR AYAT-AYAT SEMESTA DAN MENINGKATNYA POSISI BAHASA ARAB DALAM TAFSIR AL-QUR’AN (Q. 76: 17) - Muammar Zayn Qadafy (STAI AL-ANWAR SARANG, 2017)
The main idea this article explores is that the knowledge on Arabic language plays great role on the scientific Quranic exegesis. As sample, Agus Purwanto's Nalar Ayat-Ayat Semesta is chosen, merely on his interpretation on the Q. 76: 17. This research also finds Purwanto's three foundations thatemphasize the miraculous side of the Arabic language which the Quran speaks with: (1) the Paradigm of a Sains Islamâ€; (2) the dependency on the lexical meaning of the keywords; (3) the authors Contextualizing the meaning to only current context by ignoring its original context. This research also describes how an interpretation which depends on the knowledge of Arabic language looks like. Keywords: Tafsir Ilmi, Bahasa Arab, Metodologi